Analisis Pemanfaatan Media Sosial Dalam Sustainable Tourism Desa Pulau Gadang - Ivan Taufiq; Daherman, Yudi (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2025)
Sustainable Tourism can be defined as a tourism concept that is expected to ensure the preservation and authenticity of natural resources. It is a development concept of sustainable development that includes economic, sociocultural, and environmental aspects in order to meet the needs of the present without reducing the fulfillment of the needs of future generations and can form a society that is adaptive to the environment and interacts with each other. Online media is important in its implementation, so this research looks at how social media can be a step in sustainable tourism. This research uses a descriptive qualitative method in which the object of research is the management of social media as sustainable tourism. The results of the study found that the village of Pulau Gadang in managing social media as sustainable tourism is as a validity tool and village promotion, education as a principle of sustainability, community and collaboration, responsible tourism management, interaction, evaluation and reciprocity.